Pelatihan Pembuatan Pop Up Book Sebagai Media Pembelajaran Calistung Bagi Guru UPT SDN 10 Rembon, Lembang Palesan, Kecamatan Rembon - Irene Hendrika Ramopoly; Charlie Baka (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Based on the results of interviews with principals and teachers at UPT SDN 10 Rembon, Lembang Palesan, Rembon Sub-district conducted in August 2022, several problems were obtained in the learning process in the classroom, including: low interest and motivation in learning students in participating in Calistung learning. This causes there are still about 30 students from the total of grades 1-3 who are not fluent in reading, writing, and arithmetic. In addition, another factor is the lack of teacher awareness in the use and use of learning media, teachers lack skills and experience in creating, utilizing, and using learning media, especially in teaching students to read, write, and count. In addition, so far there has been no special socialization for teachers related to the use and use of learning media. The use and use of learning media is very important to achieve learning objectives, and is able to make the learning environment conducive and fun for students. One of the appropriate learning media that can be applied based on problem analysis at partner locations is Pop Up Book-based learning media. The purpose of this training is to support teacher skills in creating, utilizing, and using Pop Up Books as learning media that can be used in Calistung learning. The methods used in this PKM activity include: 1) Preparation; 2) Manufacturing Training; 3) Evaluation and Monitoring. The mandatory output target to be achieved in this training is in the form of articles that will be published in a national journal with ISSN (Comserva journal) in 2023.